Pemberdayaan Peningkatan Produksi Tembakau Mojo Melalui Kegiatan Penyuluhan Hama dan Penyakit Pada Tanaman Tembakau - Abdillah, Achlish; Pratama, Hendra; Retnaningnastiti, Rezita; Anaqah, Salsabila; Eza, Gabriella Lintang; Prasetya, Nada; Masyrofi, Muhammad Zukhrofi Ardi (Idea Pengabdian Masyarakat, 2024)
Mojo Village is one of the villages located in Padang District, Lumajang Regency. The area of Mojo Village is 5.50 km2. Mojo Village has an altitude of 100-500 meters above sea level. To improve the standard of living and income of the people of Mojo village carry out farming activities. One of them is growing Tobacco. Mojo tobacco is the mainstay tobacco from Lumajang district. However, in this case, many farmers do not understand the problems surrounding tobacco cultivation. From this condition, it stimulates UNEJ KKN students to bridge between the government and tobacco farmers so that they can work together and be organized between sectors. KKN 448 UNEJ tries to explain the role of agricultural extension as an effort to increase understanding of pests and diseases for farmers, making E-books, and also making Associations. The objective to be achieved from the implementation of this program is to increase the knowledge, production and productivity of tobacco farmers so as to support the process of sustainable agricultural development, Then the most important thing is to increase the income and standard of living of tobacco farmers while increasing economic activity in other sectors.